THE COMPARATIVE ANALYSIS OF METHODS FOR ASSESSING THE IMPACT OF OPERATIONAL RISK ON BANKS’ CAPITAL - Lavreniuk, Vladyslav; Prymostka, Liudmyla; Sokolovska , Natalia; Prymostka, Andrey (Socio-economic relations in the digital society, 2024)
The aim of the study is to compare international and national approaches to measuring the impact of operational risk on bank capital, to identify the advantages and the level of complexity of each approach, and to reveal the level of strain on banks’ regulatory capital. The study found a significant impact of operational risk on the sufficiency of banks’ capital, highlighting the need to form substantial capital reserves to absorb potential losses. A detailed comparative analysis of banks, including PrivatBank, Oschadbank, and Ukreximbank, indicated a significant influence of the size of banking assets on the amount of capital under operational risk. The study revealed differences in measuring the impact of operational risk on the regulatory capital of a bank depending on the use of international (BIA, TSA) or national approaches to assessing potential losses. The results of the study show a substantial difference in the assessment of reserves under operational risk using international and national approaches. This difference indicates the need for a more harmonized approach to the assessment and management of operational risk in the banking sector. The national approach to assessing reserves under operational risk creates more strain on banks’ capital compared to international approaches. It was determined that the most significant difference in assessing the minimum capital for covering operational risk is observed between the international approach BIA and the national approach. It was established that the banks’ priority task is to minimize reserves under operational risk in order to reduce the strain on bank capital, which can only be achieved by building and maintaining an effective operational risk management system by the banks.